Rancang Bangun Sistem Informasi Manajemen Distribusi Ijazah Pada Universitas Dinamika Bangsa - Xaverius (Jurnal PROCESSOR, 2021)
Management of diploma management in Universitas DinamikaBangsa is still conventional, the data collection process is still written manually. Part related to the management of diploma namely BAAK (Administrative Bureau of Academic and Student Affairs), Prodi Staff, Kaprodi(Head of Study Program), Chairman and Vice Chairman I. BAAK in charge of printing diploma then Staff Prodi duty to equip and distribute diploma to student. Kaprodi in charge of distributing diplomas that have not been taken one year. Every process in the making of diploma is not well recorded, such as diploma that has not been printed because the data is not complete student or diploma which not yet complete because not yet signed by student concerned. The purpose of this research is to design a management information system of distribution of diploma, so that every procedure and transition of diploma is recorded historically. Development of this information system using object-oriented approach includes the stages of problem formulation, data collection, system analysis, modeling and prototyping.